Determination of the Relationship Between C-Reactive Protein (CRP) Levels and Hepatitis B Surface Antigen (Journal of Environmental Bioremediation and Toxicology, 2022)
The relationship between hepatitis B virus (HBV) infection and C-reactive protein (CRP), which is an inflammatory biomarker, is limited in studies on the general population. Thus, this study aimed at determining the relationship between CRP levels and Hepatitis B surface antigen in patients with hepatitis B. A total of 70 samples were screened for the presence of hepatitis surface antigen by one step hepatitis B Surface antigen test strip (serum/plasma) package insert. The samples were further subjected to ELISA test and quantitative real time PCR to determine the viral load. The performance of the assay on the 70 samples showed 17 (24.29%) patients were positive and 53 (75.71%) patients were negative for serological test. Out of the 17 samples which were positive for HBV, CRP was positive in 5 patients while 12 patients were negative for CRP. While out of 53 patients who were negative for HBV, 9 were positive for CRP and 44 were negative for CRP. For the significance of viral load for clinical monitoring, three titer groups were presented. Among the 70 samples tested for viral load of HBV, 50% (35/70) of samples showed low titer by the Ct˂30, while only 15.71% (11/70) of samples were detected with high viral load by Ct˃30. Statistical analysis showed insignificant relationship between CRP and HBV.  Positive predictive value of CRP was lower;it is revealed that the presence of HBV infection cannot be predicted on the basis of CRP analysis only. The reason behind lower CRP concentration in HBV positive cases remains unclear but there is a perception that high CRP levels in the blood can be a marker of inflammation.
Keywords: C-reactive protein; Hepatitis B; Surface antigen; Elisa; Viral load